Somatic embryogenesis for Hevea: The technique of anther culture - Seneviratne P; de Zoysa G M; Nugawela A; Wijesekera G A S; Withanage S P (Journal of the Rubber Research Institute of Sri Lanka, 1996)
Production of pollen plants via somatic embryogenesis might be cultivar dependent as successful production of pollen plants is reported only by Chinese Scientists. None of the locally available clones of Hevea produced even somatic embryos. The slow progress made on adoptation of this technique suggests difficulties in reproducing, may be due to various critical factors involved in the process. The rate of callus formation was influenced by the amount of auxins and cytokinins in the medium and the presence of both types was important for initiation of callus
Keywords: Anther; Hevea; Rubber; Somatic embryogenesis